An Analysis of Language Style in the "Maleficent 2: Mistress of Evil" Movie (Sociolinguistics Approach) - Rika Artika Br Sinulingga (Journal of Language Education (JoLE), 2024)
Language Style is the formal construct of the language used to communicate with other people. This study aims to analyze the types of language styles used and the dominant type used in “Maleficent 2: Mistress of Evil” movie. The source of the data was taken from the script of “Maleficent 2: Mistress of Evil” movie. The research design is descriptive qualitative research. The analysis is based on the five language styles adopted from Martin Joos’ (1976) theory; they are frozen style, formal style, consultative style, casual style and intimate style. The result shows 77 data, there are 11 frozen styles, and 5 formal style. 35 casual relationships, 10 consultative styles, and 11 intimate styles. It means, that the Casual language style is the most dominant type of language style in the movie Maleficent 2 (2019) because the movie Maleficent is a movie that tells the relation between good mother and daughter is so warm and tries to reconcile the two kingdoms, where almost conversation in the use of informal language and share about the relationship between all the character.